Efficient Biomimetic Hydroxylation Catalysis with a Bis(pyrazolyl)imidazolylmethane Copper Peroxide Complex. Issue 49 (12th October 2015) - Wilfer, Claudia; Liebhäuser, Patricia; Hoffmann, Alexander; Erdmann, Hannes; Grossmann, Oleg; Runtsch, Leander; Paffenholz, Eva; Schepper, Rahel; Dick, Regina; Bauer, Matthias; Dürr, Maximilian; Ivanović‐Burmazović, Ivana; et al.
Abstract: Bis(pyrazolyl)methane ligands are excellent components of model complexes used to investigate the activity of the enzyme tyrosinase. Combining the N donors 3‐ tert ‐butylpyrazole and 1‐methylimidazole results in a ligand that is capable of stabilising a (μ‐η 2 :η 2 )‐dicopper(II) core that resembles the active centre of tyrosinase. UV/Vis spectroscopy shows blueshifted UV bands in comparison to other known peroxo complexes, due to donor competition from different ligand substituents. This effect was investigated with the help of theoretical calculations, including DFT and natural transition orbital analysis. The peroxo complex acts as a catalyst capable of hydroxylating a variety of phenols by using oxygen. Catalytic conversion with the non‐biological phenolic substrate 8‐hydroxyquinoline resulted in remarkable turnover numbers. In stoichiometric reactions, substrate‐binding kinetics was observed and the intrinsic hydroxylation constant, k ox, was determined for five phenolates. It was found to be the fastest hydroxylation model system determined so far, reaching almost biological activity. Furthermore, Hammett analysis proved the electrophilic character of the reaction. This sheds light on the subtle role of donor strength and its influence on hydroxylation activity. Abstract : Enhancing reactivity : Efficient catalysis is shown by a copper peroxide tyrosinase model complex consisting of pyrazolyl and imidazolyl moieties. The important role of the third N donor function (turquoise in figure) is highlighted in a reactivity study including a Hammett analysis.